Study of the Most Valuable Researcher: Bibliometric Indicators and Collaboration Networks - Peña Ramírez, Camilo (2021)
This work seeks to find the Most Valuable Researcher (MVR) within the academics of Faculties of Engineering and Business of a University in Chile, applying bibliometric indicators and collaboration networks. The methodology consisted in reviewing the literature referring to similar bibliometric studies from open databases, such as SciELO and Google Scholar. As a result of the study, a model was proposed based on the main bibliometric indicators used, with it was possible to filter the researchers from both faculties and establish a ranking with those academics with the best results and the current situation facing the research in each unit. This ranking indicates the standard that the most valuable researchers have, identifying that the variable “collaborative networks” has a direct relationship with the productivity of researchers and, also, the existence of correlations with indicators of network grade, co-authorship, and research area. This work seeks to deliver recommendations on the quantity and quality of scientific production within the University. Future research should include other databases and expand the scope by region, country, and area of expertise, and consider other factors such as the age of the researcher, forms of citation, and characteristics by area of knowledge, as well as deepen the concept of MVR, and its virtuous effect on the productivity of an academic unit.